Toward Self-Measures in Cochlear Implants: Daily and “Homemade” Impedance Assessment - Parreño, Matias; Di Lella, Federico A.; Fernandez, Florencia; Boccio, Carlos M.; Ausili, Sebastian A. (Frontiers in Digital Health, 2020)
Introduction Cochlear implant (CI) impedance reflects the status of electro neural interphase, acting as a biomarker for inner ear injury. Most impedances shifts are diagnosed retrospectively because it is only measured in clinical appointments, with unknown behavior between visits. Here we study the application and discuss the benefits of daily and remote impedance measures with a software specifically designed for this purpose. Methods We designed a software to perform CI impedance measurements without the intervention of health personnel. Ten patients were recruited to self-measure impedance for 30 days at home, between CI surgery and activation. Data was transferred to a secured online server allowing remote monitoring. Results All patients successfully performed measurements at home without supervision. Only 1 measurement was not performed due to software or hardware issues. Data was successfully and securely transferred to the online server. No adverse events, pain or discomfort was reported by participants. Discussion This work overviews a flexible and high configurable platform for self-measurement CI impedance. This novel approach, simplifies the CI standard of care by reducing the number of clinical visits, proving useful and constant information to the CI experts.